AN ANALYSIS OF ASCVD RISK IN A FOOD INSECURE POPULATION THROUGH COMMUNITY-BASED SCREENINGS IN WEST CHICAGO - Ethan Belnap, BS (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Cardiovascular disease (CVD) is the leading cause of death in the United States and globally. Literature demonstrates that individuals of lower socioeconomic status and those with additional social determinants of health (SDOH), such as food insecurity, have a higher incidence of atherosclerotic cardiovascular disease (ASCVD) risk factors such as: hypertension, hyperlipidemia, diabetes, and obesity. However, there remains a paucity of literature investigating the influence of SDOH on the development of ASCVD. This study seeks to analyze the prevalence of modifiable ASCVD risk factors in a food insecure population in Chicago. Furthermore, this study aims to utilize ASCVD risk to evaluate the need for preventative cardiometabolic screening and risk factor mitigation in food insecure populations. Methods: The Cardiometabolic Health Initiative (CHI) is a student-led organization focused on addressing CVD in food insecure communities in Chicago. From August 2023-March 2024, CHI has screened 120 clients of a food pantry. Screenings included a targeted medical history, point-of- care lipid profiles, A1C, blood pressure, and 10-year ASCVD risk score. This information is utilized to provide individualized health coaching. Results: Of the 120 total patients screened, 96 patients (80%) were hypertensive. Forty-eight of the 87 patients who were screened for cholesterol (55%) had an LDL value greater than 100 mg/dL. Of the 90 patients who received an A1c screening, 36 patients (40%) had an A1C of 5.7-6.4% while 11 patients (12%) had an A1C greater than 6.5%. 87 patients had sufficient data to calculate a 10-year ASCVD score; of which 38 (43%) were less than 5%, 5 (6%) were 5-7.5%, 24 (28%) were 7.5-20%, and 20 (23%) were greater than 20%. Conclusions: Of the food insecure patients screened, our data indicates a high prevalence of hypertension, dyslipidemia, and diabetes. Nearly half of the patients screened were found to have a 10-year ASCVD risk score categorized as intermediate or high risk. These findings suggest the need for robust preventative screening and risk factor mitigation within food insecure populations.